Assessing the Sustainable Potential of Corrugated Board-Based Bundle Packaging of PET Bottles: A Life Cycle Perspective—A Case Study - Roman Jannes; Pieter Vanhauwermeiren; Peter Slaets; Marc Juwet (Clean Technologies, 2023)
Large amounts of PET bottles are used worldwide as primary packaging for numerous liquids, including water and soft drinks. In many cases, between two and eight of such bottles are bundled for transport and sales using plastic collation shrink film. This study evaluates paper-based alternatives for plastic bundling material using a life cycle assessment (LCA) of four different types of bundle packaging: LDPE shrink film, recycled Low-Density Polyethylene (rLDPE) shrink film, Ecogrip (existing paper-based bundle packaging) and Ecobundle (new paper-based bundle packaging). The study focuses on the case of bundling six bottles of 1.5 L of sparkling water. The most environmentally friendly option is identified, taking into consideration the material usage, effects on human health and effects on the biosphere. It is concluded that the new corrugated board-based bundling method (Ecobundle) is very promising. Further optimization of the design, minimization of material, improved choice of materials and improved design of the production machinery may result in a corrugated board performing even better than rLDPE shrink film in terms of the global warming potential.